Is living in African cities expensive?. Issue 12 (12th July 2019) - Nakamura, Shohei; Harati, Rawaa; Lall, Somik V.; Dikhanov, Yuri M.; Hamadeh, Nada; Oliver, William Vigil; Rissanen, Marko Olavi; Yamanaka, Mizuki
ABSTRACT: Although several studies have examined why overall price levels are higher in richer countries, little is known about whether there is a similar relationship at the urban and city level across countries. This paper compares the price levels of cities in Sub-Saharan Africa with those of other regions by analyzing price information collected for the purpose of calculating official purchasing power parities. The approach of the paper is to readjust the calculated price levels from national to urban levels, using known price-level ratios between those areas. The results indicate that African cities are relatively more expensive, despite having lower income levels. The price levels of goods and services consumed by households are 25 to 28 percent higher in Sub-Saharan Africa than in other low- and middle-income countries, relative to their income levels. Such high costs of living could constrain livelihood of low-income urban residents, as well as the development of Africa's urban economies.